STUDENTS’ MOTIVATION IN LEARNING ONLINE OF READING COMPREHENSION NARRATIVE TEXT THROUGH GOOGLE CLASSROOM - Novia Wulan Ari; testiana deni wijayatiningsih; dodi mulyadi (Universitas Galuh, 2021)
This article aims to describe the students’ motivation in learning online narrative text on students’ reading comprehension through Google Classroom of 24 students tenth-grade students at SMK Muhammadiyah Kradenan. This study used pre experimental design one group pre-test post-test and conducted at May 2020. The data was obtained through pretest, posttest and questionnaire. The data of this current study were analyzed by using SPSS consisted reliability, validity, T- test and percentage (questionnaire). The result from this article showed the students’ motivation in learning online narrative text using Google Classroom also got positive responses and they learned with high motivation. It can be concluded that there was a different result before the treatment and after the treatment. Therefore, there was students’ motivation in learning online narrative text on students’ reading comprehension through Google Classroom.